INVESTIGATING MATHEMATICS ACHIEVEMENT: AN ANALYSIS OF EFFECT SELF-EFFICACY REGARDING DIFFERENCE GENDER OF CUT SCORES - IIK NURHIKMAYATI; DADANG JUANDI (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Mathematics learning achievement is influenced by the determination of minimum completeness criteria or cut scores which are the limits of student learning mastery scores as a measure of the achievement of the specified competencies. The cut score becomes a reference for teachers and students in achieving learning outcomes. This study aims to determine how students' chances of learning achievement are influenced by their self-efficacy and gender differences based on the set cut score. This is qualitative research using statistical analysis of a linear log model. This study describes systematically the analysis of the relationship between self-efficacy and mathematics learning outcomes based on gender differences with the best model offered by the results of the linear log statistical test. The subjects of this study were 192 junior high school students in Majalengka Regency, West Java, Indonesia. The selection of research subjects was carried out using a purposive sampling technique based on the research objectives in the form of the diversity of self-efficacy and student gender. All variables in this study are categorical variables classified based on the variable type and arranged in a contingency table. The results showed that the conditional association model was suitable for use in this research case with two interactions that occurred, namely (1) gender with learning outcomes in mathematics and (2) self-efficacy with learning outcomes in mathematics. Based on the analysis of the model obtained, three probability values can be concluded in general, namely: (1) the chances of female students having mastery in learning mathematics are greater than male students; (2) the chances of students with high self-efficacy are 3.99 times greater in getting mastery in learning mathematics, and (3) the chances of students with moderate self-efficacy are 2.06 times greater in getting mastery in learning mathematics.